EFFECT OF SOME ESSENTIAL OIL AND ORGANIC ACIDS ON BLOOD PICTURE , LIPID PROFILE AND INTESTINAL HEALTH IN BROILER CHICKENS - Saad M. H.; S. S. Hameed; A. J. Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The objectire of the present study was to investigate the effect of nutritional additive of associated phytogenic P.E.P. and organic acids supplemented in drinking water on their, blood parameters, lipid profile and intestinal histomorphology in broilers. For this purpose, 240 chicks (Ross-308) one-day old were divided randomly into 6 equal groups each group 40 chicks as follow. G1supplemented with( 0.015 cc Essential Oil (EO) with Aromatic Oil (AO) 0.5cc/L) , G2 add (AO 2cc/L) ,G3 was mix (EO 0.06cc with AO 1,5cc/L) ,G4(0.03 EO with1cc AO/L ,G5 0,12cc EO /L and control (G6) group was fed the basal diet ,the results of blood parameters were indicated significant (P≤0.05) increase in amount of WBC,RBCs, hemoglobin and PCV in groups 3, 4 and 5 compared with the control , also revealed significant increased (P≤0.05) of HDL-cholesterol concentration in G3 and G4 but decreased in triglyceride, total and low density lipid concentrations were influenced by the dietary treatments in G4,3,2 and VLDL in G3 and 5.also exposed significant (P≤0.05)increased in the height and thickness of villus and crypt depth in all parts of small intestine of G3,G4 and G5 compare to the control group. In conclusion the mix Essential Oil and Aromatic Oil supplementation to the broiler diet improve blood picture (RBCs .WBCs,Hb and PCV) and enhanced with maintenance the function of the small intestine .